Optimization of profenofos degradation by a novel bacterial consortium PBAC using response surface methodology. (May 2015) - Jabeen, Hina; Iqbal, Samina; Anwar, Samina; Parales, Rebecca E.
Abstract: Profenofos (PFF), an organophosphate (OP) insecticide, has been widely used for last two decades to control insect pests. Extensive use of this toxic pesticide is leading to serious environmental consequences which impose development of methods to reduce the environmental burden of PFF using an environmental friendly and cost effective approach. In this study, a PFF degrading bacterial consortium PBAC consisting of Achromobacter xylosoxidans, Pseudomonas aeruginosa, Bacillus sp. and Citrobacter koseri, was developed. Interestingly, compared to pure isolates, the consortium degraded PFF more efficiently. Following a 2 3 full factorial central composite design based on Response Surface Methodology (RSM), different culture conditions were optimized for PFF degradation. The optimal pH, temperature and inoculum size were found to be 6.83, 34.59 °C (∼35 °C) and 0.59 g L −1 respectively to achieve maximal degradation of PFF (93.39%). Analysis of the degradation products revealed that 4-bromo-2-chlorophenol (BCP) was the major metabolite of PFF which was further metabolized to simpler products. Importantly, PBAC was capable of degrading a wide range of OP and other pesticides which renders it a useful tool for remediation of soil with a cocktail of contaminants. Graphical abstract: Highlights: We propose an efficient bacterial consortium (PBAC) for degradation of profenofos. Response Surface Methodology was employed for a well optimized degradation model. The bacterial consortium hydrolysed profenofos to 4-bromo-2-chlorophenol (BCP). BCP was further degraded to simpler and harmless products. PBAC is an efficient tool for bioremediation of profenofos and other pesticides.